Bone fractures from generalized convulsive seizures and status epilepticus—A systematic review. (25th April 2019) - Grzonka, Pascale; Rybitschka, Anja; De Marchis, Gian Marco; Marsch, Stephan; Sutter, Raoul
Abstract: Objective: We present a systematic review of the literature regarding types and anatomic distribution of fractures in association with generalized convulsive status epilepticus (GCSE) and convulsive seizures in adult patients accompanied by an illustrative case of a patient with GCSE and diffuse postictal pain from underlying bone fractures. Methods: The library search engines PubMed and EMBASE were screened systematically using predefined search terms. All identified articles written in English were screened for eligibility by two reviewers. The preferred reporting items for systematic reviews and meta‐analyses guidelines were followed. Results: The screening of 3145 articles revealed 39 articles meeting the inclusion criteria. Among all fractures, bilateral posterior fracture‐dislocations of the shoulders were reported most frequently (33%), followed by thoracic and lumbar vertebral compression fractures (29%), skull and jaw fractures (8%), and bilateral femoral neck fractures (6%). Risk factors for seizure‐related fractures are seizure severity, duration of epilepsy, the use of antiseizure drugs known to decrease bone density, and a family history of fractures. Based on these findings, a three‐step screening procedure is proposed to uncover fractures in the postictal state. All studies were retrospective without standardized screening methods for seizure‐associated fractures resulting in a very low level of evidence and a high risk of bias. Significance: Posterior fracture‐dislocations of the shoulders, thoracic and lumbar vertebral compression, fractures of the skull and jaw, and bilateral femoral neck fractures are most frequently reported. Preventive measures including bone densitometry, calcium/vitamin D supplementation, and bisphosphonate therapy should be reinforced in epilepsy patients at risk of osteoporosis. As long as the effect of standardized screening of fractures is not investigated, it is too early to integrate such a screening into treatment guidelines. In the meantime, clinicians are urged to heighten awareness regarding seizure‐associated fractures, especially in patients with postictal pain, as symptoms can be unspecific and misinterpretation may impede rehabilitation.